2023
DOI: 10.3390/pharmaceutics15030803
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Epigallocatechin as a Scaffold for Drug Development against Flaviviruses

Abstract: Arboviruses such as Dengue, yellow fever, West Nile, and Zika are flaviviruses vector-borne RNA viruses transmitted biologically among vertebrate hosts by blood-taking vectors. Many flaviviruses are associated with neurological, viscerotropic, and hemorrhagic diseases, posing significant health and socioeconomic concerns as they adapt to new environments. Licensed drugs against them are currently unavailable, so searching for effective antiviral molecules is still necessary. Epigallocatechin molecules, a green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Green tea ( Camellia sinensis ) is regarded as the second most popular drink in the world and is extensively researched, and used, for its pharmacologically active components, including anti-inflammatory properties, and remedial effects for diabetes, Alzheimer’s disease, oral cancer and dermatitis [ 158 ]. Recently, Coronado et al identified that epigallocatechin 46 and epigallocatechin gallate 47 , natural occurring polyphenols present in green tea, and their derivative EGCG octaacetate 48 ( Figure 19 ) are able to inhibit flaviviruse proteases within the sub-micromolar range [ 159 ]. Surprisingly, although all compounds share a common scaffold, they have exhibited different binding modes with 46 exhibiting a competitive inhibition behavior, while 47 and 48 are non-competitive inhibitors, possibly acting on an allosteric site.…”
Section: Natural Compounds As a Source Of Novel Antiviral Drugsmentioning
confidence: 99%
“…Green tea ( Camellia sinensis ) is regarded as the second most popular drink in the world and is extensively researched, and used, for its pharmacologically active components, including anti-inflammatory properties, and remedial effects for diabetes, Alzheimer’s disease, oral cancer and dermatitis [ 158 ]. Recently, Coronado et al identified that epigallocatechin 46 and epigallocatechin gallate 47 , natural occurring polyphenols present in green tea, and their derivative EGCG octaacetate 48 ( Figure 19 ) are able to inhibit flaviviruse proteases within the sub-micromolar range [ 159 ]. Surprisingly, although all compounds share a common scaffold, they have exhibited different binding modes with 46 exhibiting a competitive inhibition behavior, while 47 and 48 are non-competitive inhibitors, possibly acting on an allosteric site.…”
Section: Natural Compounds As a Source Of Novel Antiviral Drugsmentioning
confidence: 99%